Measurement of Charged Current Inclusive Muon Antineutrino Interactions and 2p2h Contribution using the NOvA Near Detector - Bashar, Saqib. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Physics.; Advisor: William Mann.; Committee: Hugh Gallagher, Gary Goldstein, and Gregory Pawlowski.; Keywords: Particle physics, and Nuclear physics and radiation.